Wetting and spreading kinetics of liquid Sn on Ag and Ag3Sn substrates. (15th January 2017) - Liashenko, O.Y.; Hodaj, F.
Abstract: The isothermal wetting and spreading of liquid Sn on Ag and Ag3 Sn substrates are studied for the first time using the dispensed drop technique under high vacuum at 300° and 400 °C. The Sn/Ag3 Sn interaction involves only dissolution of Ag3 Sn in the molten phase while the Sn/Ag interaction involves both dissolution of Ag and Ag3 Sn formation at the interface. Only one spreading regime is observed in Sn/Ag3 Sn system and two spreading regimes in Sn/Ag system. The contact angles of liquid Sn on Ag and Ag3 Sn substrates are evaluated and a mechanism of reactive spreading in the liquid Sn/Ag system is proposed. Graphical abstract: